Serotonin 2c receptor RNA editing in major depression and suicide. (December 2013) - Lyddon, Rebecca; Dwork, Andrew J.; Keddache, Mehdi; Siever, Larry J.; Dracheva, Stella
Abstract Objectives. mRNA for serotonin 2C receptor (5-HT2CR) undergoes editing which results in numerous isoforms. More highly edited isoforms exhibit decreased function. We recently found greater 5-HT2CR editing in suicide victims with prior bipolar disorder (BPD) or schizophrenia (SZ) compared with non-suicide patients and normal controls (NC). This study compares suicides and non-suicides with major depressive disorder (MDDSuic and MDDNoSuic) and non-suicide NC. Methods. mRNA editing was assessed in prefrontal cortex of 24 MDDSuic, 21 MDDNoSuic, and 56 NC using next generation sequencing. mRNA expression of 5-HT2CR and editing enzymes (ADAR1-2) was assessed by real-time PCR. Results. Editing was lower in MDDNoSuic than in MDDSuic, which did not differ from NC. No differences in the 5-HT2CR or ADAR1 expression were detected. ADAR2 expression was higher in NC than in MDD subjects, but did not differ between MDDNoSuic and MDDSuic. Conclusions. Our findings suggest the presence of two factors associated with 5-HT2CR editing. One factor, which probably stems from decreased ADAR2 expression, is linked to MDD and is associated with less editing. The other, seen also in our previous study of suicide in BP and SZ, is linked to suicide alone and is associated with more editing and, therefore, less receptor function.